Marketing communication in ASEAN: A bibliometric analysis - Dipa, Adzkia Kirana; Mayasari, Mayasari; Khang, Nguyen Tan; Poedjadi, Maudy Rizkiana; Priyatna, Centurion Chandratama (Universitas Padjadjaran, 2024)
Background: Due to the dynamic competition and development of marketing communication, countries in the ASEAN region need integrated collaboration between countries to combine and take advantage of opportunities that modern marketing communication practices in ASEAN countries combine sustainability, ethics, and cultural practices. Purpose: This study aims to systematically analyze and classify research articles and then visualize them. Method: A comprehensive discussion of the development of marketing communications from the past to the present can be done by conducting research using Bibliometric Analysis. The research dataset was processed and analyzed using R Language and Biblioshiny software. This research examines 302 documents from 1991 to 2023 covered in the study period (32 years), taken from the Scopus dataset source. Result: The number of publications from year to year has increased significantly; for the last 32 years, 2023 was the peak publications of marketing communication articles, and Indonesia, Malaysia, and Thailand are the countries with the largest contribution to the production of research articles in the field of marketing communication in the ASEAN region. Conclusion: Collaboration between ASEAN countries is facilitated by geographical proximity, cultural similarities, and the maturity of research networks in several countries that dominate this region. Implications: Further research can be conducted to identify marketing communication research topics that are most often the focus of collaboration and to determine priority topics for the future.